Renewable Energy Inclusion on Economic Power Optimization using Thunderstorm Algorithm - A.N. Afandi; Goro Fujita; Yunis Sulistyorini; Nedim Tutkun (Proceeding of the Electrical Engineering Computer Science and Informatics, 2017)
This paper presents an economic operation considered renewable energy which is optimized using thunderstorm algorithm. The problem is constrained by an emission standard and various technical limits implemented on the 62-bus system model. Simulations showed that the renewable energy inclusion penetrates to the unit commitment of generating units with strongly approach for the computational solution. This inclusion also affects to the individual power production in accordance to the fuel cost and pollutant discharge.